A multi‐environment analysis of winter faba bean germplasm for cover crop traits. (29th June 2021) - Brasier, Kyle; Smither‐Kopperl, Margaret; Bullard, Valerie; Young‐Matthews, Anna; Bartow, Amy; Friddle, Mara; Bernau, Christopher; Humphrey, Mathew; Dial, Heather; Wolf, Mary; Hu, Jinguo; Zakeri, Hossein
Abstract: Faba bean ( Vicia faba L.) cultivars for cover cropping have remained unchanged in the western United States over the past century. Although breeding efforts have improved grain production across much of the world, improvement of the crop for cover crop applications (e.g., biomass production at the flowering stage) remains understudied. Therefore, a trial of nine newly developed faba bean lines from the USDA‐ARS and four commercial checks ('Bell Bean', 'V4', 'V5', and 'Windsor') was established to evaluate cover crop traits across six diverse testing environments. The experiment revealed significant genotype × environment interactions for winter vigor, nitrogen (N) concentration, and aboveground N yield. Significant genotypic variation was observed for important cover crop traits including winter vigor, spring vigor, aboveground biomass, and aboveground N yield, whereas variation for percentage of N derived from the atmosphere was primarily determined by the testing environment. The study also identified a strong association between early plant vigor and aboveground biomass ( r = .71), which offers potential increases in breeding efficiencies. In addition, advanced faba bean lines from the USDA‐ARS were shown to produce twice the biomass of Bell Bean across testing environments, and faba bean line PS18301 produced at least 20% more aboveground N yield in five out of the six environments than the conventionally used cover crop cultivars Windsor and Bell Bean. Faba bean lines in this study may be used by cover crop breeders as parent materials. Core Ideas: Breeding efforts have potential to improve faba bean materials for cover cropping. Significant genotype x environment interactions were observed for many cover crop traits. Trait–trait associations may improve breeding efficiency for cover crop faba bean.